2014
DOI: 10.4304/jltr.5.1.46-55
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Use of Student Portfolios to Develop Students’ Metacognition in English as a Foreign Language Learning

Abstract: Abstract-In this research, it is proposed that student portfolios should be used as a mediated tool in English as a foreign language (EFL) education. It aimed to study to what extend student portfolios could assess and develop students' metacognition in language learning. A total of 53 Thai secondary students of English were divided into a control and an experimental group. Their attitudes toward language learning were assessed through pre-and post-intervention questionnaires. The students in the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The process of reviewing, comprehending, and assessing the many aspects of the problems may give light to the manner in which implementations evolve, develop, and integrate with one another. According to Abhakorn (2014), the use of e-portfolios incorporates the potential to expand the teaching of writing skills and track the development of the learners. In addition, the usage of e-portfolios enables the sharing of work among students.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The process of reviewing, comprehending, and assessing the many aspects of the problems may give light to the manner in which implementations evolve, develop, and integrate with one another. According to Abhakorn (2014), the use of e-portfolios incorporates the potential to expand the teaching of writing skills and track the development of the learners. In addition, the usage of e-portfolios enables the sharing of work among students.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Studies on the development of metacognition proposed three approaches to develop metacognition: 1) cognitive theory of instruction 2) humanistic theory of self-directed learning, and 3) socio-cultural theory of social interaction and mediation (1,46).…”
Section: Linguodidactics and Methods Theoretical Description Of The Language For Learning Purposesmentioning
confidence: 99%
“…Another was the study conducted by Abhakorn (2014), on investigating the use of student portfolios to develop students' metacognition in English as a foreign language learning. The results indicated that the understanding of metacognition development through a mediated tool in language learning, and suggest EFL teachers and language educators to be aware of the importance of metacognition and reflective skills training in order to reach the full potential of the portfolio approach in language learning to be realized.…”
Section: Iiirelated Literaturementioning
confidence: 99%